Selection and validation of reference genes for quantitative gene expression normalization in Taxus spp. - Kaikai Zhang; Wei Fan; Duanfen Chen; Luyuan Jiang; Yunfeng Li; Zhiwang Yao; Yanfang Yang; Deyou Qiu (Scientific Reports, 2020)
Abstract Quantitative real-time PCR (qRT-PCR) is commonly used to measure gene expression to further explore gene function, while suitable reference genes must be stably expressed under different experimental conditions to obtain accurate and reproducible data for relative quantification. Taxol or paclitaxel is an important anticancer compound mainly identified in Taxus spp. The molecular mechanism of the regulation of taxol biosynthesis is current research goal. However, in the case of Taxus spp., few reports were published on screening suitable reference genes as internal controls for qRT-PCR. Here, eight reference genes were selected as candidate reference genes for further study. Common statistical algorithms geNorm, NormFinder, BestKeeper, ΔCt, and RefFinder were used to analyze the data from samples collected from a cell line of Taxus × media under various experimental conditions and from tissues of Taxus chinensis var. mairei. The expression patterns of TcMYC under salicylic acid treatment differed significantly, with the best and worst reference genes in the cell line. This study screened out suitable reference genes (GAPDH1 and SAND) under different treatments and tissues for the accurate and reliable normalization of the qRT-PCR expression data of Taxus spp. At the same time, this study will aid future research on taxol biosynthesis-related genes expression in Taxus spp., and can also be directly used to other related species.